Exploring internal stakeholders' emotional attachment & corporate brand perceptions through corporate storytelling for branding - Brighton Nyagadza; Ernest M. Kadembo; Africa Makasi (Cogent Business & Management, 2020)
The goal of this article was to explore internal stakeholders' emotional attachment and corporate brand perceptions through corporate storytelling for branding. Due to the nature of the research questions, the research was purely qualitative in nature. A total of fifty four (54) in-depth semi-structured interviews were conducted from 2019 to 2020. These constituted the bedrock of qualitative data analysis for the study. An interpretivist research paradigm, anchored on subjectivist ontology, were both applied as research philosophy pillars. This was done by the researchers in order to get deeper understanding of corporate stories for branding in the six (6) selected listed company. Purposive sampling was used to select respondents from three (3) levels of authority, thus operational, tactical and strategic level. The mutual connection on variables of corporate stories for branding and Impression Management theory elements depicted that these are related to internal stakeholder's corporate brand perceptions. The research results showed that there is a positive nexus between corporate stories for branding with emotional attachment and internal stakeholders' corporate brand perceptions. Recommendations include that corporate management need to consciously involve internal stakeholders in developing corporate stories for branding, as it is crucial in carving positive corporate brand perceptions and emotional attachment. The research contributes to the theory and practice by shaping listed corporates to be able to maximise effectiveness of their corporate strategies, meant to improve internal corporate reputation and motivation of internal stakeholders.
Keywords: M3; M31; 650; emotional attachment; listed companies; corporate storytelling for branding; internal stakeholders; perceptions; Zimbabwe